Conceito de integral: uma proposta computacional para seu ensino e aprendizagem - Melo, José Manuel Ribeiro de (2002)
The teaching and learning of Differential and Integral Calculus, taken as fundamental in Exact Sciences courses, has been focused throughout time as a traditional methodological practice, based on definitions, theorems, properties, examples and exercises. This methodology has been contributing to a very high number of giving up and failure in such courses. One of the possibilities of trying to revert this, is the use of new computerized technologies as a didactic tool in Calculus courses. This work has aimed the creation and use of activities, all fundamented in cognition theories and in the main historical elements of Integral, to be developed in a computerized atmosphere. A qualitative type methodology has been chosen and it was based on a sequence of teaching and working in pairs in a computer lab. The choice of working in pairs is based on the fact that it leads to dialogues, changing of ideas and conclusions in a much more spontaneous way. The computer is used to give meaning to the concept of Integral. The different steps were created with the purpose of allowing students to develop the elements which would lead to such concept. During the activities students have used the computer in different steps.This use permitted the process of visualizing, simulating and deepening in the mathematical thought, some guesses and its contradictions or validations. The results of having had the sequence of teaching applied show that in a computerized atmosphere the teaching and learning are much more meaningful, contextualized and motivating for students as well as for teachers